The importance of the domestic workers’ constitutional amendment for the consolidation of labor rights - Manoel, Aparecida; Caruso, Sergio (JRG Journal of Academic Studies, 2023)
The purpose of this article is to demonstrate the relevance of Constitutional Amendment 72 of 2013 - PEC das domestics to ensure the labor rights of the domestic employee. It emphasizes that the concept of domestic servant from colonial Brazil to imperial Brazil, there was no legal definition. The first legal concept in our country came about with the Municipal Posture Code of São Paulo 1916, conceived as domestic servant that individual who performs his function at home, has no economic purpose, since the domestic worker carries out his activities to receive a salary for bear your expenses and that of your family. Domestic work in Brazil was included in Brazilian labor legislation only with Law No. 5,859, of December 11, 1972. However, this law did not fully contemplate domestic workers, as it only guaranteed them three rights, including the registration of this employee to the Social Security System. In turn, the Brazilian Constitution of 1988, although it has advanced in relation to the domestic worker, with some guarantees and achievements such as Article 7 in item I, on equal rights between the sexes and that no domestic worker will be subjected to torture, in order to reduce occupational risks in the performance of their functions, among others. However, the 1988 Constitution denied these workers several rights guaranteed in relation to other employees of other categories. Therefore, it did not fulfill its essence of equality among workers, therefore, it cannot be considered a citizen constitution. The article is outlined as follows, at first presenting the conception of domestic employment and later an approach to domestic work legislation in Brazil, in order to discuss the main changes that have occurred in the domestic employee's law. The main authors consulted in this article were Cristo (2015), Damasceno and Chagas (2013) and Silva (2016). The article is scientific research of bibliographical nature. In view of this, only with the Household PEC that domestic servant really had several relevant achievements, social rights foreseen and incorporated into the new regulation of article 7 of the Constitution, which were not guaranteed by the 1988 Magna Carta.